PENYELESAIAN SENGKETA TATA USAHA NEGARA DI BIDANG PENGADAAN BARANG DAN JASA YANG BERKEPASTIAN HUKUM - Sri Yudyaningrum, Khoirunissa; Damayanti, Suci (Puslitbang Hukum dan Peradilan MA bekerja sama dengan Ditjen Badimiltun MA, 2023)
This article aims to analyze the consistency of the judges of Administrative Court (PTUN) on adjudicating cases of government procurements (PBJ) in order to create legal certainty. There’s two issues that will be discussed, first, how legal certainty construction relates with how Administrative Courts adjudicate government deeds of procurement cases; and two, how the effort of the judges of Administrative Court on establishing legal certainty on adjudicating governments deeds on procurement cases. To answer the issues, the research uses the empirical or non-doctrinal methods that analyze how law is applied in reality, including study about the verdict. The verdict that we use for this study will restricted in procurements cases, especially in construction field. The research shows that the judges of Administration Courts being inconsistent on their judgements causes irregularity of law. This is in addition to being influenced by the expansion of the meaning of state administrative decisions (KTUN) in the Government Administration Law, as well as the inconsistency of judges in interpreting any KTUN in the PBJ field which is the absolute authority of the PTUN. Including when interpreting whether or not efforts to rebut and rebut appeal in PBJ disputes.